Strengthening the competitiveness of presto milkfish through increasing entrepreneurial spirit and packaging innovation - Aditya Nizar Al Ardi; Aulia Nadhirah; Dinu Saadillah; Dewi Kurniawati; Fredy Eka (Community Empowerment, 2024)
MSMEs play a crucial role in the Indonesian economy, absorbing 97% of the total workforce. Despite the significant contribution of MSMEs to the Indonesian economy, there is a lack of competitive capabilities among them. One of the MSME products in Jember Regency that currently demands attention is presto milkfish. However, there are several issues, including the suboptimal entrepreneurial spirit among MSME players and unattractive product packaging. To address these challenges, it is essential to enhance the value and skills in packaging design for presto milkfish products. The activity involved delivering material on the value of entrepreneurship and providing training in creating packaging designs for presto milkfish products. The results of the service activities indicate an increased awareness and instillation of entrepreneurial values among presto milkfish MSMEs, as shown by questionnaires filled out before and after the training. The participants' knowledge has improved, leading to increased motivation to operate their businesses. MSME players have successfully designed their product packaging and implemented it in their businesses.